Germination of Populus ciliata Seed as influenced by Moisture Stress - Singh, R. V.; Singh, Virendra (Indian Forester, 1983)
Hazard reduction for fire prevention in forest areas can be achieved by reducing the quantity, breaking the continuity and disturbing the arrangement of forest fuels. Factors affecting the build-up of fire hazard have been described and an over-view of the possible techniques of hazard reduction in Indian forests has been presented. It has been concluded that properly maintained fire-lines can help in breaking the continuity of the fuels but they cannot he relied upon to contain and localise the fires by themselves. Planting of fire resistant species in covered firebreaks holds greater promise and such species need to be identified for different areas. Silviculural practices like weeding, cleaning, thinning etc. and agri-silvicultral practices can help considerably in reducing fire hazard. Need for refining the technique of prescribed burning through research on fire behaviour under variable conditions, thorough training of personnel and close supervision of the operation has been stressed.